The Level of Propensity to Use the Internet in Enterprises in European Union Countries in 2019 - Maciej OESTERREICH (Communications of International Proceedings, 2021)
The main purpose of the article was to analyse the level of propensity to use the Internet in enterprises of individual EU member states. For this purpose, data on the use of information and communication technologies (ICT) and e-commerce in enterprises run annually by Eurostat were studied. Due to the multidimensional nature of the analysed phenomenon its measurement was based on a synthetic taxonomic measure constructed with the TOPSIS method. The conducted research shows that there are clear differences between individual EU countries in the level of propensity to use the Internet in enterprises. However, they do not result directly from the wealth of societies.
Keywords: Use the Internet in enterprises; European Union; propensity; TOPSIS